Catalytic Performance of MIL‐88B(V) and MIL‐101(V) MOFs for the Selective Catalytic Reduction of NO with NH3. Issue 3 (14th December 2020) - Li, Shengchen; Zhai, Ying; Wei, Xiaxia; Zhang, Zhe; Kong, Xiangfei; Tang, Fushun
Abstract: In this paper, the SCR properties of MIL‐88B(V) and MIL‐101(V) MOFs materials by hydrothermal synthesis were investigated, and the effect of the coordination and spatial topology of MOFs materials on the coordination state, chemical state and surface properties of V ions, as well as the relationship with SCR catalysis, were discussed. The results showed that the NO conversion of MIL‐88B(V) can be as high as 80 %, while those of MIL‐101(V) can only reach to 20 %, but the SCR reaction selectivity of both were excellent. The coordination structure and spatial topological structure of MOFs materials had a great influence on the coordination state, chemical state and surface properties of V ions, resulting in different SCR catalytic performance. The reaction performance of SCR was related to the structural properties of V3 Ox units and followed the E‐R mechanism. The staggered and layer upon layer close‐packed structure of MIL‐88B(V) made the density of V3 Ox unit cluster higher and the distance of adjacent V3 Ox unit cluster smaller. More V 5+ ions and V−O−V bonds can form more Brønsted acid sites, also was conducive to the progress of the SCR reaction. Although MIL‐88B(V) has insufficient high temperature stability, but its good SCR reaction selectivity and SCR catalytic performance at medium and low temperature can still have the application prospect of medium and low temperature industrial denitration in non‐electric industries. Abstract : A selective catalytic reduction : Due to the coordination between BDC and Cl ions, the valence state of V ions mainly exists in the form of 5 valence, the dense VOx structure in MIL‐88B(V) contains a large number of V−O−V structures, resulting in more Brønsted acid sites, so MIL‐88B(V) has an excellent SCR catalytic performance.